Blue cooperative luminescence properties in Yb3+ doped GeO2-PbO-Bi2O3 vitreous system for the production of thin films - Cacho, V. D.; Kassab, L. R. P.; Oliveira, S. L.; Mansano, R. D.; Verdonck, P. (Elsevier B.V., 2006)
Germanate glasses are of interest for optoelectronic applications because they combine high mechanical strength, high chemical durability and temperature stability with a large transmission window (400 to 4500 nm) and high refractive index (2.0). GeO2-PbO-Bi2O3 glasses doped with Y-b(3+) were fabricated by melting powders in a crucible and then pouring them in a brass mold. Energy Dispersive Spectroscopy showed that the glass composition has a high spatial uniformity and that the Yb concentration in the solid sample is proportional to the Yb concentration in the melt, what was confirmed by absorption measurements. Intense blue emission at 507 nm was observed, corresponding to half of the wavelength of the near infrared region (NIR) emission; besides, a decay lifetime of 0.25 ms was measured and this corresponds to half of the decay lifetime in the infrared region; these are very strong indications of the presence of blue cooperative luminescence. Larger targets have been produced to be sputtered, resulting in thin films for three dimensional (3D) display and waveguide applications. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: bulk glasses; cooperative effect; germanate; rare-earth